2013
DOI: 10.1128/jvi.01967-13
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Interleukin-6 in the Expression of PD-1 and PDL-1 on Central Nervous System Cells following Infection with Theiler's Murine Encephalomyelitis Virus

Abstract: bInfection with Theiler's murine encephalomyelitis virus (TMEV) in the central nervous system (CNS) of susceptible mice results in an immune-mediated demyelinating disease which is considered a relevant viral model of human multiple sclerosis. We previously demonstrated that the expression of positive costimulatory molecules (CD40, CD80, and CD86) is higher on the microglia of TMEV-resistant C57BL/6 (B6) mice than the microglia of TMEV-susceptible SJL/J (SJL) mice. In this study, we analyzed the expression lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 46 publications
1
33
2
1
Order By: Relevance
“…By contrast, studies using the BeAn-TMEV strain have shown that excessive IL-6 promotes pathogenic Th17 responses and viral persistence by preventing apoptosis of virus-infected cells [5,112]. IL-6, in interplay with other cytokines, also contributes to T cell exhaustion and inadequate viral elimination in TME [113,114]. However, sole IL-6 reduction following IL-10R neutralization is apparently insufficient to alter local CNS inflammatory responses in the present study.…”
Section: Discussioncontrasting
confidence: 76%
“…By contrast, studies using the BeAn-TMEV strain have shown that excessive IL-6 promotes pathogenic Th17 responses and viral persistence by preventing apoptosis of virus-infected cells [5,112]. IL-6, in interplay with other cytokines, also contributes to T cell exhaustion and inadequate viral elimination in TME [113,114]. However, sole IL-6 reduction following IL-10R neutralization is apparently insufficient to alter local CNS inflammatory responses in the present study.…”
Section: Discussioncontrasting
confidence: 76%
“…A). Moreover, when we performed flow cytometric analysis of splenic cells with CD45 + CD11b + phenotype, common to macrophages and dendritic cells, we noticed a marked increase in the population of CD45 + CD11b + cells of PPEE‐treated splenocytes for both concentrations (7.0 ± 0.90% at 31.3 µg mL, −1 Fig. B, and 6.9 ± 0.30% at 62.5 µg mL, −1 Fig.…”
Section: Resultssupporting
confidence: 64%
“…OASL1 causes T-cell suppression in persistent lymphocytic choriomeningitis virus infection of mice and is regarded as a new target for preventing chronic infectious diseases (43,44). In agreement with this idea, subpopulations of CNS-infiltrating macrophages have been demonstrated to reduce protective antiviral immunity by inducing T-cell exhaustion that leads to virus persistence in TMEV-infected mice (31). Besides this, M2-polarized cells have the ability to reduce antiviral immunity as described for human cytomegalovirus infection (1).…”
Section: Discussionmentioning
confidence: 76%